2009
DOI: 10.1007/s11605-009-1050-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Curative Intent Liver Surgery is Safe and Effective for Recurrent Colorectal Liver Metastasis: Results from an International Multi-institutional Analysis

Abstract: Repeat CIS for recurrent colorectal liver metastasis can be performed with low morbidity and near-zero mortality. Patients with no extra-hepatic disease are best candidates for repeat CIS. In these patients, repeat CIS can offer the chance of long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 52 publications
(81 reference statements)
9
128
1
9
Order By: Relevance
“…Repeat hepatectomy is independently associated with favorable long-term outcome in patients with colorectal liver metastases in the repeat hepatectomy group remain to be clearly identified, with a plethora of significant prognostic variables identified in different studies [6,7,10,15,16,[18][19][20][21][22].…”
Section: Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Repeat hepatectomy is independently associated with favorable long-term outcome in patients with colorectal liver metastases in the repeat hepatectomy group remain to be clearly identified, with a plethora of significant prognostic variables identified in different studies [6,7,10,15,16,[18][19][20][21][22].…”
Section: Original Researchmentioning
confidence: 99%
“…There were 308 (63.1%) men and 180 (36.9%) women. At index hepatectomy, the median number of tumors on preoperative imaging was two (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Tumor size ranged from 5 to 150 mm, with a median size of 35 mm.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the efficacy of repeat surgical resection or ablation for the treatment of colorectal liver metastasis and hepatocellular carcinoma; however, there is a paucity of data on the management of recurrent ICC. [16][17][18] Given this, the objective of the current study was to characterize the treatment of patients with recurrent ICC and define therapy-specific outcomes. Specifically, using a large multi-institutional cohort of patients, we sought to determine the rate and the pattern of recurrent disease following curative-intent surgery for ICC, as well as define the therapy-specific outcome of patients treated for recurrent disease.…”
mentioning
confidence: 99%
“…However colorectal cancer (CRC), the third most common cancer worldwide, commonly metastasizes to the liver, which is the leading cause of CRC mortality. 3,4 The current therapeutic options for HCC and liver metastasis from CRC (LM-CRC) include surgery (resection and liver transplantation) and local (ablative) therapy. Unfortunately, less than 20% of HCC patients are eligible for curative procedures 5 because most of them have advanced disease at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%